Role of store-operated Ca2+ entry and STIM2 in retinal neurodegeneration during glaucoma - Baranykova, Sofiia (Frontiers in Aging Neuroscience, 2025)
Ca2+ homeostasis is essential for glial cell activity and normal neuronal function, and store-operated Ca2+ entry (SOCE) is one mechanism that maintains it. The present review discusses the interplay between Ca2+ dysregulation and microglial activation in glaucomatous retinal degeneration. We examine the impact of Ca2+ homeostasis and SOCE on microglial function and their potential role in retinal ganglion cell degeneration and present the hypothesis that SOCE dysregulation may underlie glaucomatous pathology. This review suggests that targeting Ca2+ pathways in microglial cells can be a potential treatment for glaucoma.